Effects of porcine somatotropin administration and its duration on growth performance and carcass characteristics of finishing swine fed to 280 lb - Johnston, M.E.; Schricker, B.R.; Nelssen, Jim L.; Goodband, Robert D.; Hines, Robert H.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred eight barrows with an initial weight of 120 lb were utilized to determine the effects of porcine somatotropin (PST) administration period and duration on growth performance and carcass characteristics of finishing swine fed to 280 lb. Pigs were injected daily in the extensor muscle of the neck with either a placebo or 4 mg pST. Treatments included: (A) placebo injection from 120 to 280 lb; (B) pST injection from 120 to 280 lb; (C) pST injection from 120 to 230 lb and then placebo injection from 230 to 280 lb; (D) placebo injection from 120 to 230 lb and then pST injection from 230 to 280 lb; (E) placebo injection from 120 to 170 lb, pST injection from 170 to 230 lb, and then placebo injection from 230 to 280 lb; and (F) placebo injection from 120 to 250 lb and then pST injection from 250 to 280 lb. All pigs were fed a corn-soybean meal diet containing 1.2% lysine. Performance data were collected and evaluated for three weight ranges: 120 to 230 Ib, 230 to 280 lb, and 120 to 280 lb. Two pigs from each pen were slaughtered to determine carcass characteristics. The first pig was slaughtered at 230 lb and the second pig at 280 lb . Average daily gain (ADG), average daily feed intake (ADFI), and feed conversion (F/G) were all optimized when pigs were treated with pST for the entire time from 120 to 230 lb and from 120 to 280 lb. Longissimus muscle area (LEA), backfat thickness, percentage carcass muscle, and kidney fat were all improved at 230 lb when pigs were injected with pST. There was no difference in these carcass traits when pigs were injected with pST from 120 to 230 lb compared to pigs treated with pST from 170 to 230 lb. These same carcass characteristics measured in pigs slaughtered at 280 lb showed significant improvement with pST treatment compared to the control. However, when pST treatment lasted the entire trial (120 to 280 lb), there was significant improvement in carcass characteristics over pST treatments of shorter duration. Whole ham weight was unaffected by pST treatment at either slaughter weight, but trimmed ham weight was improved by pST treatment at 230 lb. Daily protein accretion rate (DPA) and daily fat accretion rate (DFA) were optimized at both slaughter weights by pST treatment that lasted for the duration of the trial. Organ weights were increased by pST treatment but were unaffected by administration period or duration of pST treatment. These data indicate that growth performance and carcass characteristics were maximized when pST was administered continually from 120 to 280 lb.
Keywords: Swine; Repartition; GF; Performance; Carcass; Heavy weight